The role of cognitive behavioural therapy in living well with COPD - Heslop-Marshall, Karen (Breathe (Sheff), 2019)
Psychological ill health is very common in COPD; CBT may be a key step towards improving the care of COPD patients http://ow.ly/fb8j30onfPj